Pemanfaatan E-Commerce Untuk Mendorong Generasi Muda Menjadi Wirausaha Baru Pada Siswa SMA Negri 105 di Kelapa Dua Wetan, Jakarta Timur - Sari Puspitarini (Jurnal Pengabdian Masyarakat Nasional, 2023)
Electronic commerce or E-commerce or in Indonesian Electronic Commerce is all buying and selling activities carried out through electronic media. Therefore E-commerce activities include distributing, selling, purchasing, marketing products (goods and services), by utilizing telecommunications networks such as the internet, television, or other computer networks. Although the means include television and telephone, E-commerce is now more common via the internet. State Senior High School 105 is one of the secondary schools that educates its students in carrying out school activities, so that they are programmed and directed according to its mission "Fostering Student Independence Through Planned and Continuous Entrepreneurship Habituation and Self-Development Activities". For this reason, in this community service activity, students are expected to be able to utilize technology through e-commerce to be able to encourage and help students to recognize their potential so that it can be developed optimally.So far, SMA Negeri 105 students have used e-commerce. However, the students felt that they did not have the courage and were not able to determine and seize opportunities to do entrepreneurship. Therefore we are motivated to share knowledge through counseling programs to these students regarding the use of E-Commerce to encourage the younger generation to become new entrepreneurs as a provision for students in planning their business in the future.Keywords: E-commerce; Entrepreunership; Motivated